Efforts to Resolve Rental Disputes Renting Market Land Rent Back (Supreme Court Cassavior Decision) - Manullang, Zulkifli; Tri Bawono, Bambang (TABELLIUS: Journal of Law, 2025)
Abstract. The purpose of this study is to determine and analyze the form of the lease agreement for the Gladak Market land that is being re-leased which can protect the interests of the parties and to determine and analyze the settlement of the lease dispute for the Gladak Market land including the yard and yard that are re-leased by the tenant. This type of research is normative legal research. The approach method in this study is the case approach (case approach). The type and source of data in this study are secondary data. Secondary data is data obtained by researchers from the literature which is the result of research. The data analysis method used is qualitative data analysis, meaning that in writing the thesis it only contains descriptions and does not use statistical data and mathematical figures. As a way to draw conclusions from the results of the research that have been collected, the normative-qualitative normative analysis method will be used, because this study is based on existing regulations as positive legal norms. The results of the study indicate that legally the form of a written lease agreement has a stronger legal basis, especially if a dispute occurs, because the parties can use the written agreement as a basis for resolving disputes that have a strong legal basis. And for the purposes of evidence in court, the ideal form is an agreement made before an authorized official or notary, so that it can be an authentic deed. Keywords: Dispute; Existing; Regulations; Resolution.